Orthoptera (Tettigoniidae and Acridoidea) from Miombo woodlands of Central Tanzania with the description of new taxa - Hemp, Claudia; Heller, Klaus-Gerhard (Zootaxa, 2019)
A list of the Orthoptera of Miombo woodlands of the Manyara, Dodoma and Tabora Regions of Tanzania is presented. 64 Ensifera species were recorded of which two genera (Kefalia n. gen. with three species newly described; Sentia n. gen., 1 species) and Melidia adfinia n. sp. are new to science. Further 4 new species of Acrometopini are described from the area (Horatosphaga laticerca n. sp., Horatosphaga scalata n. sp., Peronura wottae n. sp., and Tenerasphaga mpwapwae n. sp.). 78 Acridoidea species were recorded. Miombo woodlands are vanishing rapidly these days so that faunal information will become an important tool to measure habitat quality of a certain forested area and for restauration measures. The species Peronura wottae n. sp. and Kefalia grafika n. sp. must be considered as Critically Endangered since only known from Wotta Forest Reserve on the Mpwapwa plateau. This forest reserve is heavily degraded by illegal cutting and lifestock grazing and will disappear in the near future if no immediate measures are taken by responsible authorities.